Exposure Time of Silica Dust and the Incidence of Oxidative Stress, Inflammation, and Fibrosis in Rat Lungs - Artana, I. Gusti Ngurah Bagus; Artini, I. Gusti Ayu; Arijana, I. Gusti Kamasan Nyoman; Rai, Ida Bagus Ngurah; Indrayani, Agung Wiwiek (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Until now, exposure to silica dust is still a health problem worldwide. Silica exposure in the lungs will cause pulmonary fibrosis which is initiated by inflammation. However, the results of several studies regarding the duration of inflammation and fibrosis are still inconsistent. There was a role of oxidative stress in silicosis, but there were also inconsistencies in terms of when oxidative stress occurs in silica exposure. AIM: This study aimed to study the toxic effects of silica dust exposure by looking at the picture of inflammation and fibrosis and malondialdehyde (MDA) levels in lung tissue during the observation period of 7 days, 14 days, 21 days, and 28 days. METHODS: This study used a randomized post-test only control group design. The research sample was male Wistar rat (Rattus norvegicus), aged 6–10 weeks, body weight 150–200 g (divided into 5 groups: Control group, day 7 group, group day 14, group day 21, and group day 28). We administered silica suspension through intratracheal injection of 30 mg/rat on 0.5 mL of volume. Examination of MDA level was using the ELISA technique; histopathological examination of the liver used hematoxylin-eosin (HE) staining to determine inflammation and fibrosis. Statistical test using one-way ANOVA or Kruskal–Wallis followed by post hoc test. RESULTS: The results of our study found that intratracheal silica exposure increased MDA levels on the 7th day, increased the accumulation of collagen from the 14th day, and increased the pulmonary inflammation score on the 14th day (p < 0.05). CONCLUSIONS: It was concluded that silica exposure caused significant oxidative stress on day 7 as well as significant inflammation and pulmonary fibrosis on day 14.